Association analysis of stem rust resistance in U.S. winter wheat - Zhang, Dadong; Bowden, Robert L.; Yu, Jianming; Carver, Brett F.; Bai, Guihua (My University, 2014)
Stem rust has become a renewed threat to global wheat production after the emergence and spread of race TTKSK (also known as Ug99) and related races from Africa. To elucidate U.S. winter wheat resistance genes to stem rust, association mapping was conducted using a panel of 137 lines from cooperative U.S. winter wheat nurseries from 2008 and simple sequence repeat (SSR) and sequence tagged site (STS) markers across the wheat genome. Seedling infection types were evaluated in a greenhouse experiment using six U.S. stem rust races (QFCSC, QTHJC, RCRSC, RKQQC, TPMKC and TTTTF) and TTKSK, and adult plant responses to bulked U.S. races were evaluated in a field experiment. A linearization algorithm was used to convert the qualitative Stakman scale seedling infection types for quantitative analysis. Association mapping successfully detected six known stem rust seedling resistance genes in U.S. winter wheat lines with frequencies: Sr6 (12%), Sr24 (9%), Sr31 (15%), Sr36 (9%), Sr38 (19%), and Sr1RS[superscript Amigo] (8%). Adult plant resistance gene Sr2 was present in 4% of lines. SrTmp was postulated to be present in several hard winter wheat lines, but the frequency could not be accurately determined. Sr38 was the most prevalent Sr gene in both hard and soft winter wheat and was the most effective Sr gene in the adult plant field test. Resistance to TTKSK was associated with nine markers on chromosome 2B that were in linkage disequilibrium and all of the resistance was attributed to the Triticum timopheevii chromosome segment carrying Sr36. Potential novel rust resistance alleles were associated with markers Xwmc326-203 on 3BL, Xgwm160-195 and Xwmc313-225 on 4AL near Sr7, Xgwm495-182 on 4BL, Xwmc622-147 and Xgwm624-146 on 4DL, and Xgwm334-123 on 6AS near Sr8. Xwmc326-203 was associated with adult plant resistance to bulked U.S. races and Xgwm495-182 was associated with seedling resistance to TTKSK.
Citation: Zhang D, Bowden RL, Yu J, Carver BF, Bai G (2014) Association Analysis of Stem Rust Resistance in U.S. Winter Wheat. PLoS ONE 9(7): e103747. https://doi.org/10.1371/journal.pone.0103747
Keywords: Stem rust; Winter wheat; U.S. winter wheat; Resistance genes